The Effectiveness of Serial Pictures in Enhancing Students’ Reading Comprehension of Descriptive Texts - Virda Rizki Ananda; Ratna Sari Dewi; Siti Nurul Azkiah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates the effectiveness of the Serial Pictures Technique in enhancing reading comprehension of descriptive texts among eighth-grade students at Junior High School Jakarta. Employing a quasi-experimental design, the research involved an experimental group taught using the Serial Pictures Technique and a control group receiving traditional instruction. Pre-tests and post-tests were administered to measure students' reading comprehension. The results indicated that the experimental group significantly outperformed the control group, with a mean score increase from 45 to 70, compared to the control group's increase from 48 to 62. Statistical analysis confirmed a significant difference (p = 0.035) and a modest effect size (Cohen's d = 0.36), suggesting that the Serial Pictures Technique effectively improves students' reading comprehension. These findings highlight the importance of innovative teaching methods in enhancing language skills.